KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI EDUKATOR DALAM MENINGKATKAN KREATIVITAS GURU PADA SMP NEGERI 1 BANDA ACEH - Amiruddin .; Cut Zahri Harun; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The leadership of a principal as an educator should have a power to guide teachers and students, to develop education professionals, to follow the updates of technology, and to demonstrate teaching skill. This study aimed at finding out: principal leadership to develop teachers’ skill in designing lesson plan, teachers’ responsibility in teaching, and teachers’ commitment in supervising and evaluating the teaching and learning process. This study employed a descriptive method with qualitative approach. The data collection techniques used were observation, interview, and documentation. The subjects of the study were the principal and teachers. The results: (1) Program to elevate learning quality, the implementation process of the program is presented in the preparation process of designing teaching instruments such as syllabus, annual program, semester program, and lesson plans. These instruments are main tool which should be prepared by teachers before they start teaching; (2) Principal leadership in terms of developing teachers’ responsibility in teaching was done in a persuasive way; and (3) Principal leadership in dealing with teachers’ commitment in the process of doing supervision and evaluation towards teaching and learning process is done with paternalistic leadership. This was done to level up teachers’ creativity without any compulsion. Keywords: Leadership, Educator, and Teachers’ Creativity.